APOE4 impairs macrophage lipophagy and promotes demyelination of spiral ganglion neurons in mouse cochleae - Junru Chen; Haibing Chen; Qinjun Wei; Yajie Lu; Tianming Wang; Xiuhong Pang; Guangqian Xing; Zhibin Chen; Xin Cao; Jun Yao (Cell Death Discovery)
Abstract The ApoE-ε4 gene is a well-established genetic risk factor for neurodegenerative diseases, such as Alzheimer’s disease and multiple sclerosis, which are characterized by axonal demyelination in the central nervous system. Recent studies have implicated ApoE-ε4 in age-related hearing loss (ARHL), suggesting a potential role of APOE4 isoform in peripheral nervous system degeneration. However, the role of APOE4 in ARHL are still unclear. In this study, we explored the potential role of APOE4 in axonal demyelination of spiral ganglion neurons (SGNs). ApoE-ε4/ε4 (APOE4) and ApoE-ε3/ε3 (APOE3) mice were used to characterize SGNs. The effect of APOE4 on phagocytosis and autophagy as well as intracellular cholesterol level was evaluated in resident cochlear macrophages (RCMs) and mouse bone marrow-derived macrophages (BMDMs). The results showed that significant axonal demyelination was observed in SGNs of 10-month-old APOE4 mice, accompanied by the presence of myelin debris engulfed by RCMs. Meanwhile, inhibited phagocytosis of myelin debris and impaired lipophagy were detected in APOE4 RCMs and APOE4 BMDMs with an aberrant accumulation of lipid droplets (LDs), which could be reversed by trehalose treatment. This study provided a deep insight into the pathogenesis of APOE4-induced axonal demyelination of SGNs associated with the impaired lipophagy in RCMs, which helped to elucidate the underlying mechanism of ApoE-ε4 in ARHL.